A thermodynamic framework for the modeling of crystallizable triple shape memory polymers. (January 2019) - Moon, S.; Cui, F.; Rao, I.J.
Abstract: Triple shape memory polymers (TSMPs) can be programed to remember and switch between three distinct shapes with the use of external stimuli, typically an increase in temperature. In this work, constitutive equations have been developed to model the thermo-mechanical behavior of crystallizable TSMPs. In these materials the transient shapes are fixed by the formation of crystalline phases, whereas the switching between the temporary and permanent shapes is due to the melting of the crystalline phases. The model is developed using a framework based on the theory of multiple natural configurations. Constitutive equations have been formulated for the original amorphous phase, the intermediate semi-crystalline phases, and transition of the crystalline phases, during the shape fixation and recovery cycles of TSMPs. These models have been developed within a full thermodynamic framework, extending our previous work in which the models were developed within a mechanical setting (Moon, Cui, & Rao, 2015; Moon, Rao, & Chester, 2016 ). The model has been applied to solve for the problems of inflation and extension of a hollow cylinder and uniaxial extension. The results are consistent with experimental observations.